Serum total sialic acid levels as an indicator (Baghdad Science Journal, 2005)
Forty patients with acute lymphoblastic leukemia(ALL) were tested for the serum levels of total sialic acid(TSA) and the immunoglobulins before and after treatnemnt with six diffrent chemotherapy protocols while significantly